A Multiwavelength Light-curve Analysis of the Classical Nova KT Eri: Optical Contribution from a Large Irradiated Accretion Disk - Izumi Hachisu; Mariko Kato; Frederick M. Walter (The Astrophysical Journal)
KT Eri is a classical nova that went into outburst in 2009. Recent photometric analysis in quiescence indicates a relatively longer orbital period of 2.6 days, so that KT Eri could host a very bright accretion disk during the outburst like in the recurrent nova U Sco, the orbital period of which is 1.23 days. We reproduced the optical V light curve as well as the supersoft X-ray light curve of KT Eri in outburst, assuming a large irradiated disk during a nova wind phase of the outburst while a normal size disk after the nova winds stop. This result is consistent with the temporal variation of wide-band V brightness that varies almost with the intermediate-band Strömgren y brightness, because the V flux is dominated by continuum radiation, the origin of which is a photospheric emission from the very bright disk. We determined the white dwarf mass to be M _WD = 1.3 ± 0.02 M _⊙ , the hydrogen-burning turnoff epoch to be ∼240 days after the outburst, the distance modulus in the V band to be ( m − M ) _V = 13.4 ± 0.2, and the distance to KT Eri to be d = 4.2 ± 0.4 kpc for the reddening of E ( B − V ) = 0.08. The peak absolute V brightness is about ${M}_{V,{\rm{\max }}}=-8.0$ and the corresponding recurrence time is ∼3000 yr from its ignition mass together with the mean mass-accretion rate of ${\dot{M}}_{{\rm{acc}}}\sim 1× 1{0}^{-9}\,M_{\odot }$ yr ^−1 in quiescence. Thus, we suggest that KT Eri is not a recurrent nova.